Successional development of the phototrophic community in biological soil crusts, along with soil formation on Holocene deposits at the Baltic Sea coast - Kammann, Sandra; Leinweber, Peter; Glaser, Karin; Schiefelbein, Ulf; Dolnik, Christian; Mikhailyuk, Tatiana; Demchenko, Eduard; Heilmann, Elena; Karsten, Ulf (Frontiers in Ecology and Evolution, 2024)
Harsh environmental conditions form habitats colonized by specialized primary microbial colonizers e.g., biological soil crusts (biocrusts). These cryptogamic communities are well studied in drylands but much less in temperate coastal dunes, where they play a crucial role in ecological functions. Following two dune chronosequences, this study highlights the successional development of the biocrust's community composition on the Baltic Sea coast. A vegetation survey followed by morphological species determination was conducted. Sediment/soil cores of the different dune types were analyzed to uncover the potential impacts of the biocrust community on initial soil formation processes with special emphasis on biogeochemical phosphorous (P) transformations. Biocrust succession was characterized by a dune type-specific community composition, shifting from thinner algae-dominated biocrusts in dynamic dunes to more stable moss-dominated biocrusts in mature dunes. The change in the biocrusts community structure was accompanied by an increase in Chl a, water, and organic matter content in the biocrusts. 25 algal and cyanobacterial species, 16 mosses, and 26 lichens across all sampling sites were determined. The pedological characterization of these cores elucidated initial processes of soil genesis, such as decalcification, acidification, and the accumulation of organic matter with dune and biocrust development. Further, the chemistry of iron (Fe)-containing compounds such as the Fedithionite/Fetotal ratios confirmed mineral weathering and the beginning of soil profile development. The biocrusts accumulated P over time, while the P content in the underlying sediment did not change. That implies that biocrusts take up P from the geological parent material in the dunes, thereby accumulating available P in the ecosystem, which gets transferred into subsoil horizons through leaching or redeposition. The relative proportion of the bioavailable P-pool (56 to 74% of Pt) increased with dune succession. That happened at the expense of more stable bound P, which was transformed into labile P. Thus, the level of plant available P along the dune chronosequences increased due to the microbial activity of the biocrust organisms. It can be concluded that biocrusts of temperate coastal dunes play a crucial role in maintaining their habitat by accumulating nutrients and organic matter supporting soil development and subsequent vegetation.